2011
DOI: 10.1007/s12630-011-9520-8
|View full text |Cite
|
Sign up to set email alerts
|

Repeat dosing of rocuronium after reversal of neuromuscular block by sugammadex

Abstract: To the Editor, Sugammadex specifically antagonizes the steroidal neuromuscular blocking agent (NMBA), rocuronium, 1 and it also has affinity for other steroidal NMBAs. A period of 24 hr is currently recommended before re-administering rocuronium after sugammadex. A If neuromuscular block (NMB) is needed before this time interval ends, a nonsteroidal NMBA should be given; however, nonsteroidal NMBAs are not available clinically in Japan. We present herein a 35-yr-old male patient (weight 73 kg, height 173 cm) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…The clinical duration (duration from the initial administration to spontaneous recovery to 25% of control twitch height) with 0.6 mg kg -1 rocuronium bromide is 30 to 40 min [9]. In the presented case the clinical duration was within the range of what was expected for the repeat dosing of rocuronium (about 30 min), as were the observations of Matsuki et al [7]. These authors reported the re-appearance of T1 64 min after re-administration of rocuronium 1 mg kg -1 being administered 19 min later after sugammadex.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The clinical duration (duration from the initial administration to spontaneous recovery to 25% of control twitch height) with 0.6 mg kg -1 rocuronium bromide is 30 to 40 min [9]. In the presented case the clinical duration was within the range of what was expected for the repeat dosing of rocuronium (about 30 min), as were the observations of Matsuki et al [7]. These authors reported the re-appearance of T1 64 min after re-administration of rocuronium 1 mg kg -1 being administered 19 min later after sugammadex.…”
Section: Discussionsupporting
confidence: 67%
“…However, the effect produced was less intense (86% T1 block) and had a slower onset time than would normally be expected, upon which another 10 mg of rocuronium were added. On the other hand, Matsuki et al reported a case where rocuronium 1 mg kg -1 administered 19 min later after sugammadex 2.75 mg kg -1 , in a patient under sevoflurane anesthesia, was unable to induce muscular relaxationand an additional 30 mg were required [7].…”
Section: Discussionmentioning
confidence: 99%
“…There were some limitations to our study. Duration of action in Group Rocuronium 0.9 mg/kg may have been prolonged by the administration of sevoflurane in two patients [8]. Additionally, onset time may have been shortened in patients receiving ephedrine before TOF-0 was obtained as ephedrine increases cardiac output.…”
Section: Danish Medical Journal Danish Medical Journalmentioning
confidence: 99%
“…Additionally, some clinicians may be reluctant to administer sugammadex due to the challenges that may arise following a potential reoperation requiring administration of rocuronium within the first 24 hrs post-operatively [8]. Finally, sugammadex is not recommended in patients with significantly decreased kidney function (glomerular filtration rate below 30 ml/min, including dialysis) [17], and sugammadex has been correlated with a higher incidence of anaphylaxis than neostigmine [18].…”
Section: Danish Medical Journal Danish Medical Journalmentioning
confidence: 99%